Hasil dan Motivasi Belajar Siswa Menggunakan Pembelajaran Kooperatif Tipe STAD - Lalu Hasgar Simaguna; Kristayulita Kristayulita; Kiki Riska Ayu Kurniawati (Universitas Islam Negeri Sayyid Ali Rahmatullah Tulungagung, 2020)
This research aims to determine the impact of the Student Teams Achievement Division (STAD) learning model on learning outcomes and students’ motivation for learning. This type of experimental research with quasi design methods, i.e. using design research nonequivalent control group design. The subject in this research was students from class VII at MTs Islam Selaparang Putra by sampling the VII A class as an experimental class and class VII B as the control class. The research instruments are test and questionnaires. The results of the research showed that there was an impact of the STAD type learning model towards learning outcomes and students’ motivation. The average scores of learning outcomes on students using the STAD model are higher than students taught with conventional models and the students’ motivation for learning with the STAD model is higher than those with conventional models. Implications for teachers with learning STAD model learning are more organized, so that teachers can be more optimal in the learning process. Students become more active and confident because of the help of the group members and the provision of reward at the end of learning to support motivation for students in learning.